Project Based Learning: A Systematic Literature Review (2015-2022) - Ruiz Hidalgo, David; Ortega-Sánchez, Delfín (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Project Based Learning (PBL) generates interdisciplinary teaching contexts in which competency-based learning processes take precedence. PBL favours the development of students’ cognitive, linguistic and social skills, and encourages active participation, motivation and creativity. However, research on PBL acquires differential nuances in its implementation at different educational levels. This descriptive and inferential study aims at analysing didactic research published from 2015 to 2022, according to PRISMA guidelines. The results obtained report an outstanding Spanish presence in the areas of natural sciences. The results suggest a greater curricular extension of this active methodology and its attention in initial teacher training.